Practise Science Process Skills and Sprout up Environmentally Caring Attitudes Through Worksheet Base on School Gardens - Krismiyanti, lufia; Marianti, Aditya; Hartono, Hartono (Postgraduate, Universitas Negeri Semarang, Indonesia, 2019)
The study aims to analyze the effectiveness learning worksheet application to practise science process skills and sprout up an environmentally caring attitude. This research is a Research and Development (R & D). There are two stages in this study, the stage of the worksheet development and test effectiveness. In the study the effectiveness measured from the results of students’ sains process skills and the results of environmentally caring attitude test students'. The study showed that (1) the worksheet  that developed is worthy of being used as a learning device, (2) worksheet that developed effective for science process skills practise and sprout up an environmentally caring attitude towards students. The results of the t / z test of science process skills show tcount >ttable = 3,4227 > 1,2935 and the environmentally caring attitude tcount >ttable = 5,2614 >1,6665. The conclusion of the research is worksheet that developed on school garden effective for science process skills practise and sprout up an environmentally caring attitude towards students.